2005
DOI: 10.1353/jmh.2005.0187
|View full text |Cite
|
Sign up to set email alerts
|

Military Synthesis in South Asia: Armies, Warfare and Indian Society, c. 1740-1849

Abstract: Following the rapid collapse of the Mughal Empire after 1707, the Mughal Successor States attempted to modernize their state apparatus and their armies. Both the Indian kingdoms and the British-led East India Company (EIC) attempted the construction of hybrid military organizations. How, then, can one explain the continuous military victories of the EIC? For opening up new dimensions on the military supremacy of the Europeans in Afro-Asia, the analytical tool of Military Synthesis might be more useful than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…By 1820, the British and Dutch had conquered the first two, relying primarily on indigenous credit, Asian soldiers, and pre‐industrial technologies to do so. “There was no British blitzkrieg” in South Asia (Roy :657), Britain instead relying heavily on indigenous intermediaries such as the Jagat Seth banking house (Bose :26), and drawing upon the world's largest ever market for private military labor (Kolff ), to secure dominion over the subcontinent. Raffles’ defeat of the Sultans of Surakarta and Yogyakarta in Central Java during the British inter‐regnum there likewise rested on a combination of military reliance on Indian sepoys and an alliance with local collaborators (Ricklefs :113), while Batavia reverted to extensive reliance on “indirect rule” in the Dutch East Indies following a short and disastrous bid to modernize the colony following its post‐1815 return to Dutch control (Ricklefs :118).…”
Section: Rethinking the East‐west Power Shiftmentioning
confidence: 99%
“…By 1820, the British and Dutch had conquered the first two, relying primarily on indigenous credit, Asian soldiers, and pre‐industrial technologies to do so. “There was no British blitzkrieg” in South Asia (Roy :657), Britain instead relying heavily on indigenous intermediaries such as the Jagat Seth banking house (Bose :26), and drawing upon the world's largest ever market for private military labor (Kolff ), to secure dominion over the subcontinent. Raffles’ defeat of the Sultans of Surakarta and Yogyakarta in Central Java during the British inter‐regnum there likewise rested on a combination of military reliance on Indian sepoys and an alliance with local collaborators (Ricklefs :113), while Batavia reverted to extensive reliance on “indirect rule” in the Dutch East Indies following a short and disastrous bid to modernize the colony following its post‐1815 return to Dutch control (Ricklefs :118).…”
Section: Rethinking the East‐west Power Shiftmentioning
confidence: 99%
“…Much of the literature that has focused on the medieval and modern dynasties and empires of the Indian sub-continent has customarily stressed the varying military powers exercised by Bahmanis, Vijayanagars, Mughals, Reddis, Marathas, Bijapuris, Portuguese, and the British (Banaji 1932;Yazdani 1947;Ali 1997;Roy 2005). Th e following paper therefore draws on historical records and ethnographic research to correct how African Indians' infl uential roles have been downplayed.…”
Section: Introductionmentioning
confidence: 99%
“…In the Ottoman case, in particular, it has been argued recently that throughout much of the 18 th century the empire's military weakness was not "obvious" enough to provoke radical reform (for example, Aksan 2007). It has also been suggested that the ways of fighting developed in Western Europe circa 1700 did not suit some terrainsthe vast barren expanses of India or the Eurasian steppe, for example; in such cases, it was "natural" for rulers (and indeed, Western colonizers) to opt for traditional methods of warfare, or for some sort of synthesis (for example, Chase 2003;Roy 2005;Lorge 2008;Hoffmann 2015). In that case, a decision not to reform appears rational in the short term, albeit leading to grave consequences in the longer perspective.…”
mentioning
confidence: 99%